Target visibility under mesopic vision using a driving simulator. (October 2019) - Chen, Z; Tu, Y; Wang, Z; Liu, L; Wang, L; Lou, D; Zhu, X; Teunissen, K
Small target visibility is widely used to evaluate the quality of road lighting. It provides a link between lighting design and driving performance. However, it is based on a strong simplification of the driving task using psychophysical data from laboratory conditions. Using a driving simulator to mimic the real driving environment, the impact of driving workload on target detection performance in mesopic vision conditions has been evaluated. The target visibility level is studied with and without driving workload together with different luminance contrasts and target positions, with reference to the small target visibility scenario. The results show that the driving workload significantly reduces the target detection performance. Consequently, the visibility level value for driving conditions should be much higher (visibility level ≥21) than some currently recommended ones (visibility level = 7) to achieve the same detection rates. Effects of target position and contrast are found in a way consistent with the literature. In addition, results indicate that the small target visibility model used for road lighting is limited and needs to be improved for a reliable prediction of visual performance with driving workload.